Inquiry-based professional learning in the practicum: potential and shortcomings - Vieira, Flávia (2021)
The paper presents a study conducted at the authors' institution to evaluate the potential and shortcomings of an inquiry-based practicum model in post-Bologna initial teacher education master programs. Data was collected through survey questionnaires to practicum participants and the analysis of student teachers' practicum reports. Results show that the participants' views (perceived quality) and evidence from practicum reports (inferred quality) are globally aligned with the model's rationale (intended quality). The model promotes inquiry competences, multifaceted professional knowledge, and a transformative vision of education. Shortcomings of and constraints to inquiry are discussed, and future directions for enhancing it are presented.